Use of heart rate variability in monitoring stress and recovery in judo athletes - Morales, J.; Álamo, J. M.; Garcia-Massó, X.; Buscà, B.; López, J. L.; Serra-Añó, P.; González, L. M. (The Journal of Strength and Conditioning Research, 2014)
The main objective of this study was to examine the effect of different judo training loads on heart rate variability (HRV) measurements, to determine if they can be used as valid indicators in monitoring stress and recovery in judo athletes. Fourteen male national-standard judo athletes were randomly divided into 2 groups, and each group followed a different type of training, namely, a high training load (HTL) and a moderate training load program (MTL). Data collection included HRV measurements, a Recovery Stress Questionnaire for athletes (RESTQ-SPORT), and strength measurements, 4 weeks before and after the training program. The HTL group had lower square root of the mean squared difference of successive RR intervals, very low frequency, high frequency, short-term variability, short-range scaling exponents, general recovery, sport-specific recovery, general stress, maximum strength, maximum power, and higher low/high frequency ratio at posttest compared with pretest (p < 0.05). The HTL group showed lower short-range and long-range scaling exponents, general recovery, sport-specific recovery, and higher general stress than the MTL group in posttest measurements (p < 0.05). In conclusion, judo athletes enrolled in an HTL program showed an imbalance of the autonomic nervous system with decreased vagal modulation, together with a decrease in strength parameters, higher markers for stress, and a lower perception of recovery.